GRIN2B mediates susceptibility to intelligence quotient and cognitive impairments in developmental dyslexia. (February 2015) - Mascheretti, Sara; Facoetti, Andrea; Giorda, Roberto; Beri, Silvana; Riva, Valentina; Trezzi, Vittoria; Cellino, Maria R.; Marino, Cecilia
Abstract : Objective(s): Developmental dyslexia (DD) is a complex heritable condition associated with impairments in multiple neurocognitive domains. Substantial heritability has been reported for DD and related phenotypes, and candidate genes have been identified. Recently, a candidate gene for human cognitive processes, that is, GRIN2B, has been found to be associated significantly with working memory in a German DD sample. In this study, we explored the contribution of six GRIN2B markers to DD and key DD-related phenotypes by association analyses in a sample of Italian nuclear families. Moreover, we assessed potential gene-by-environment interactions on DD-related phenotypes. Materials and methods: We carried out a family-based association study to determine whether the GRIN2B gene influences both DD as a categorical trait and its related cognitive traits in a large cohort of 466 Italian nuclear families ascertained through a proband affected by DD. Moreover, we tested the role of the selected GRIN2B markers and a set of commonly described environmental moderators using a test for G×E interaction in sib pair-based association analysis of quantitative traits in 178 Italian nuclear families. Results: Evidence for a significant association was found with the categorical diagnosis of DD, performance intelligence quotient, phonemic elision, and auditory short-term memory. No significant gene-by-environment effects were found. Conclusion: Our results add further evidence in support of GRIN2B contributing toward DD and deficits in DD. More specifically, our data support the view that GRIN2B influences DD as a categorical trait and its related quantitative phenotypes, thus shedding further light on the etiologic basis and the phenotypic complexity of this disorder. Abstract : Supplemental Digital Content is available in the text.